2023
DOI: 10.3390/nu15030693
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Lipoprotein(a) Levels in Saudi Women and Its Relationship to Menopause and Adiposity

Abstract: Lipoprotein(a) is an inherent CVD risk biomarker that varies by race, and the levels of Lp(a) in Saudi women are relatively unexplored. We aimed to examine the effect of age and menopause on Lp(a) and explore the correlation between adiposity and cardiometabolic risk factors with Lp(a) in Saudi women. The third aim was to determine the predictors of elevated Lp(a) in this population. In this cross-sectional study of 229 women, we compared Lp(a) serum levels, adiposity indices, and lipid and glycemic profiles b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Losing ovarian hormones during menopause is associated with changes in adipose tissue distribution from subcutaneous to visceral regions [54].Consistent with our previous study [14],we found that postmenopausal women had higher BMI, percentage of total body fat, and fat mass than premenopausal women, which may be attributed to alterations in endogenous sex hormones as a potential mechanism of action to explain the increase in adiposity in women during menopause [55].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Losing ovarian hormones during menopause is associated with changes in adipose tissue distribution from subcutaneous to visceral regions [54].Consistent with our previous study [14],we found that postmenopausal women had higher BMI, percentage of total body fat, and fat mass than premenopausal women, which may be attributed to alterations in endogenous sex hormones as a potential mechanism of action to explain the increase in adiposity in women during menopause [55].…”
Section: Discussionsupporting
confidence: 90%
“…Premenopausal and postmenopausal women differ in age, making it challenging to separate the effects of aging from those of menopause. As noted in our previous study, age strongly predicts increased cardiovascular risk among women [14]. The mid-40s-to-50s transition to menopause is characterized by a considerable decrease in ovarian follicle counts and a corresponding decrease in estrogen levels [67].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These findings are in line with the findings of Nikkila et al who reported a higher TC among 21 elderly females. Our findings are f u r t h e r s t r e n g t h e n e d b y t h e Framingham Study, that revealed high in serum cholesterol levels in women between the premenopausal and postmenopausal stages, with the rise taking place within a short time of the 13,22 onset of the menopause. As the mean age of our female CAD cases was (57.35 years), we also attribute these higher TC and LDL to the effect of hormonal changes during post menopause,…”
Section: Assessment Of Echocardiographic Parameters (Tablesupporting
confidence: 61%
“…Various hormonal changes may also influence Lp(a) levels [ 59 ]. Conditions such as hypothyroidism, growth hormone deficiency in adults, and the depletion of endogenous sex hormones (e.g., menopause, ovariectomy, castration, orchidectomy) have been associated with increased Lp(a) concentration [ 60 , 61 , 62 , 63 ]. Conversely, hormonal replacement therapy with thyroxine or in cases of hyperthyroidism, as well as hormonal replacement treatment in postmenopausal women, have been shown to reduce Lp(a) levels in a case-dependent manner [ 64 , 65 , 66 ].…”
Section: Factors Affecting the Lp(a) Levels: Genetics And Beyondmentioning
confidence: 99%